Operation Region Selector Circuit to Obtain Maximum Efficiency of 250 W Boost Converter - Riz Rifai O. Sasue; Eka Firmansyah; Suharyanto Suharyanto (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
Interleaved boost converter gives good conversion efficiency due to its zero-current switching capability when operating in discontinuous conduction mode while keeping its input-output ripple current low. However, operating this kind of converter at interleaved operation for all the time gives poor efficiency under light-load condition. In this paper, an automatic operation region selector switch based on detection of the continuous or discontinuous current mode is proposed. With this switch, during the light-load condition, only one converter is activated, while during full-load condition both converters will be activated. The simulation results using LTspice software show that the proposed boost converter has a better efficiency compared to the conventional boost converter with efficiency range of 84.6 % to 95.32 % under various load conditions.